280 Acute Hospital Presentations among Nursing Home Residents: A Retrospective Observational Analysis. (16th September 2019) - Waters, Ruairí; Murphy, Robert; Mannion, Edel; Gaffney, Laura; Donlon, Kate; Canavan, Michelle; O'Keeffe, Shaun T
Abstract: Background: Nursing home residents are prone to acute illness due to their advancing age, underlying illnesses and immobility. The decision to refer a nursing home resident for acute hospital admission is a complex one, and there is no consensus among health care professionals about what constitutes an 'appropriate admission' to hospital from a nursing home. We aimed to explore patterns of acute nursing home patient presentations to the emergency department. Methods: This was a retrospective cohort study of emergency hospital admissions to a tertiary university teaching hospital. Emergency admissions through the emergency department were included. Elective admissions, outpatient admissions, or inter-hospital transfers were excluded. Cases were validated by scrutiny of the patient medical records, and where possible an assessment of the Rockwood clinical frailty scale (CFS) was carried out. Results: There were 126 nursing home residents who presented to ED over a two month period for emergency assessments. 87.3% (n=115) presented via ambulance. Just over half had a GP referral letter (53.2%). 72.3% of patients who presented to ED were admitted. 25.2% of patients were re-referred to ED within 30 days of hospital discharge. All patients were classified as frail. 21.3% of patients had died at the 90 day follow up mark. 66% of those with a CFS 8 or 9 died, in comparison to 16% of those with a CFS or either 6 or 7. Conclusion: We noted high numbers of patients from nursing homes attending our emergency department. A very high proportion were admitted, along with a high number of subsequent re-presentations. Death rates were higher in those with more advanced frailty status. We would suggest advanced care planning and strategies to improve the patient experience. This study highlights the requirement for improved advance care planning in the nursing home setting. This is however a complex issue. Early discussion about end of life preferences with patients and family is required.